Kreativitas Tri Broto Wibisono sebagai Seniman Tari Jawa Timur - Endang Kumala Ratih; Setyo Yanuartuti (Universitas Negeri Medan, 2020)
The discussion in this study examines the creativity of Tri Broto Wibisono who is one of the traditional dance artists in East Java. The aim of the research is to explore the process that Tri Broto Wibisono does in making a dance work so that he is able to come up with his own dance style. This study uses a descriptive analysis method that describes the creative process of Tri Broto Wibisono in making a dance work and elaborates with Sigmund Freud's psychoanalytic theory. In this research, Tri Broto Wibisono in his creative process carried out several stages, namely nyantrik (studying local dance artists), deepening the material, interpreting traditions, and new interpretations. The conclusion from the creative process of Tri Broto Wibisono is that in creating a dance, a stimulus from outside and inside is needed which will lead to an idea which is then continued by expressing it into creativity and producing a dance work that gives rise to the Tri Broto Wibisono style.